2009
DOI: 10.1164/rccm.200904-0625oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Asymptomatic Proximal and Distal Gastroesophageal Reflux on Asthma Severity

Abstract: Asymptomatic GER is not associated with distinguishing asthma symptoms or lower lung function in individuals with suboptimal asthma control who are using inhaled corticosteroids. Patients with proximal reflux report significantly worse asthma and health-related quality of life despite lack of physiologic impairment or increase in asthma symptoms. Clinical trial registered with www.clinicaltrials.gov (NCT00069823).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 33 publications
1
37
0
1
Order By: Relevance
“…While the possibility that the participants' nocturnal cough may have been related to uncontrolled asthma was not specifically addressed by the authors, the study still raises the important issue that symptoms from proximal GERD such as cough may mimic asthma and may confound measurements of asthma control in the clinical and research setting. A subgroup (n ¼ 242) of participants in the American Lung Association's Study of Acid Reflux and Asthma [Mastronarde et al 2009] underwent dual-probe pH esophageal monitoring [DiMango et al 2009]. Thirty-eight percent of participants demonstrated proximal GERD, but concordance between proximal and distal GERD on pH probe was poor.…”
Section: Pathogenesismentioning
confidence: 99%
“…While the possibility that the participants' nocturnal cough may have been related to uncontrolled asthma was not specifically addressed by the authors, the study still raises the important issue that symptoms from proximal GERD such as cough may mimic asthma and may confound measurements of asthma control in the clinical and research setting. A subgroup (n ¼ 242) of participants in the American Lung Association's Study of Acid Reflux and Asthma [Mastronarde et al 2009] underwent dual-probe pH esophageal monitoring [DiMango et al 2009]. Thirty-eight percent of participants demonstrated proximal GERD, but concordance between proximal and distal GERD on pH probe was poor.…”
Section: Pathogenesismentioning
confidence: 99%
“…The high doses of tiotropium, atropine and dexamethasone fully prevented this moderate increase in epithelial thickening. Acetylcholine stimulates the proliferation of rat airway epithelial cells through the activation of M1 muscarinic receptors and nicotinic receptors [4], an observation that may help explain the inhibitory effects of atropine and tiotropium on the epithelium thickening. A nonsignificant increase in the smooth muscle thickness was observed in mice treated with anticholinergics or dexamethasone but the weak increase in untreated mice precludes any firm conclusion on the preventive effect of these drugs.…”
Section: Discussionmentioning
confidence: 98%
“…In children with GORD and asthma-like symptoms, neutrophilia have previously been shown to positively correlate with IL-8 levels in BALF [26], and both neutrophilia and IL-8 levels were demonstrated to correlate with the number of proximal reflux events [16]. In vitro studies have revealed that muscarinic receptor stimulation, particularly the M3 receptor subtype, triggers the release of proinflammatory mediators involved in neutrophil recruitment, such as IL-8 and leukotriene (LT)B 4 , from airway smooth muscle, epithelial cells and alveolar macrophages [27][28][29]. IL-8 and LTB 4 are also involved in monocyte chemoattraction [24,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations